VD_FINDINFO Jug / 2015 / 263 vom 22. April 2015 - VD Tribunal cantonal (2015)
LÉSION CORPORELLE GRAVE, NÉGLIGENCE, DILIGENCE, RESPONSABILITÉ DU DÉTENTEUR DE VÉHICULE, TORT MORAL, PARTIE CIVILE, INDEMNITÉ PLEINE ET ENTIÈRE | 47 CO, 125 CP, 26 al. 1 LCR, 26 al. 2 LCR, 33 al. 2 LCR, 58 al. 1 LCR, 59 LCR, 62 al. 1 LCR, 3 al. 1 OCR, 308 CPC (CH), 126 CPP (CH), 433 al. 1 CPP(CH)